Pernikahan Beda Agama Sebagai Fakta Sosial Dalam Perspektif Hukum Islam - Nurhayati, Dinda Siti; Siregar, Rini Wahyuni; Arif, Muhammad; Husnayani, Rahima (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2023)
This research aims to examine islamic law's perspective on interfaith marriage as social fact. The method used is qualitative, with a descriptive approach. As a social fact, some people legalize interfaith marriages in various ways: marry abroad, marriage registration is carried out at one of the KUA or KCS with one partner "giving in" and following other's religion, marriage registration is carried out at KCS, but both partners still openly show different religious identities, recording religious leaders. In islamic studies, interfaith marriages are classified into three categories: muslim man's marriage to ahlul kitab women, and the marriage of muslim women to non-muslim men.